Review of the effects of low-velocity impact events on advanced fiber-reinforced polymer composite structures - Mani, Megavannan; Thiyagu, M.; Kumar Krishnan, Pradeep (Materials today : proceedings, 2023)
•Conventional polymer composite techniques are insufficient to viscoelastic properties.•LVI enrichment may be achieved by proper fiber selection.•Metal laminate composites are viable replacement for high-strength fiber.•Inter-facial bonding is major drawback in metal laminate composites.•Inclusion of nano particle enhances low-velocity impact strength in polymer composites. Most typical polymer composite materials have the weakest impact characteristics observed in Low-Velocity Impact (LVI) events. As a result, typical polymer composite materials are reinforced to improve their proper application attributes. The Fiber-Reinforced Polymer Composite (FRPC) materials must be converted to enhanced polymer composite structures, such as incorporating nanoparticles and selecting appropriate lamination techniques to improve the composite structure impact strength of the polymer materials. The matrix layer was created using a variety of lamination processes. The hybridization techniques with the inclusion of filler material into polymer composite structures were used to produce better results in impact kinetics for the composite structures. The quasi-static mechanical sequence approach was used to improve the LVI properties of FRPC. The inclusion ofnano-fillerparticles in polymer composites to reduce obvious low-velocity impact damage during low-velocity accidents or events is the subject of this review. This investigation aims to explore if conventional fiber materials with obvious low-velocity impact damage might be enhanced to overcome the effects of advanced FRPCs.